2016
DOI: 10.1007/978-3-319-45234-0_21
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of Factors Affecting Continuance Intention Towards Social Networking Sites

Abstract: This study examines the factors that affect consumer continuance intention to use social networking sites as a business tool. Using the Technology Acceptance Model (TAM) as the theoretical framework, the researcher tested the research model and related hypotheses using structural equation modelling. The results from a survey of 304 Facebook users in Saudi Arabia indicate that trust, perceived usefulness, and perceived enjoyment had significant positive effects on behavioural intention to continue to use social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Combining perceived enjoyment, Perceived usefulness, perceived enjoyment, and satisfaction were positively related to the intention to pay for livestream sports broadcasts online. Congruent with previous studies (Van der Heijden, 2003;Abed, 2016), the results of this study supported the hypothesis that perceived enjoyment has a positive effect on users' payment intentions, and further confirmed that perceived enjoyment is the most significant factor in motivating payment intention. The impact of users' perceived enjoyment of livestream sports broadcasts for pay appear to be stronger when there are no free broadcast alternatives unavailable.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Combining perceived enjoyment, Perceived usefulness, perceived enjoyment, and satisfaction were positively related to the intention to pay for livestream sports broadcasts online. Congruent with previous studies (Van der Heijden, 2003;Abed, 2016), the results of this study supported the hypothesis that perceived enjoyment has a positive effect on users' payment intentions, and further confirmed that perceived enjoyment is the most significant factor in motivating payment intention. The impact of users' perceived enjoyment of livestream sports broadcasts for pay appear to be stronger when there are no free broadcast alternatives unavailable.…”
Section: Discussionsupporting
confidence: 88%
“…These studies confirmed the mediating effect between perceived ease of use and behavioral intention of perceived enjoyment (Van der Heijden, 2003). The results confirmed that the intention to use a hedonic system is mostly influenced by enjoyment (Dickinger et al, 2008;Abed, 2016;Moghavvemi et al, 2017). Congruent with the previous literature, this study posited the following hypotheses: H3.…”
Section: Perceived Enjoymentsupporting
confidence: 83%
See 2 more Smart Citations
“…Saudi Arabian citizens use social media for a number of reasons including information gathering, however, it can also be used as a battleground. Abed (2016) acknowledges that a survey of 304 Saudi Arabian Facebook users identified that there was trust, a perceived usefulness and enjoyment which had significant positive behavioural effects towards social networking sites. Gunter & Elareshi (2016) identify that social media is a powerful force which is intent on infiltrating the lives of the user, however, it should also be noted that social media has become a way for users to communicate which allows users to feel more connected with others.…”
Section: The Context Of Saudi Arabiamentioning
confidence: 99%